2019
DOI: 10.1177/0969733019864162
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and validation of the Euthanasia Attitude Scale into Spanish

Abstract: Background: Considering the extensive debate that is currently taking place in Spain regarding euthanasia, it is important to examine the attitude of professionals who perform most of their duties at the bedside of these patients and their families. Objectives: The aim of the present study was to present an adaptation and validation of the Euthanasia Attitude Scale and to evaluate its psychometric properties among a sample of nursing students in Spain. Research design: A cross-sectional study design was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…The EAS total score was sensitive to years of service, frequency and number of dying patients treated, and need for training on psychological support in end-of-life patients, but not to age and gender. Onieva-Zafra also stated that beliefs of euthanasia can change and vary according to individual education and experience [ 26 ]. The same study that aimed to evaluate EAS scale psychometric properties among a sample of nursing students in Spain performed an exploratory factor analysis and found that the Kaiser–Meyer–Olkin index of sampling adequacy was 0.905 and the Bartlett’s Test of Sphericity was 2972.79 ( p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…The EAS total score was sensitive to years of service, frequency and number of dying patients treated, and need for training on psychological support in end-of-life patients, but not to age and gender. Onieva-Zafra also stated that beliefs of euthanasia can change and vary according to individual education and experience [ 26 ]. The same study that aimed to evaluate EAS scale psychometric properties among a sample of nursing students in Spain performed an exploratory factor analysis and found that the Kaiser–Meyer–Olkin index of sampling adequacy was 0.905 and the Bartlett’s Test of Sphericity was 2972.79 ( p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Examples of items are: "if a patient in severe pain requests it, a doctor should remove life support and allow that patient to die" or "it is okay for a doctor to administer enough medicine to a suffering patient to end that patient's life if the doctor thinks that the patient´s pain is too severe". The original factorial structure was composed by four dimension: severe pain [1,3,9], no recovery [4,6], patient request [8,10] and doctor´s authority [4,5,7]. Several items had cross-loaded with several dimension.…”
Section: Instrumentsmentioning
confidence: 99%
“…In Spain, as in other countries, the term euthanasia is surrounded by media controversy, colored by social, cultural and, of course, religious factors [4]. Today, there are debates about the legalization of euthanasia around the world, accompanied by a wide variety of political and ideological groups with very diverse voices, ranging from extensive pro-euthanasia campaigns to strong opponents of legalizing euthanasia.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations